Safety and efficacy of frequency-doubled Nd-YAG laser photocoagulation of different types of corneal neovascularisation (NLPC): a prospective study - Keerti Wali; Shilpa Maled; Ronak Solanki; Apoorva G Ayachit; Aniket N Shastri (BMJ Open Ophthalmology)
Purpose Frequency doubling of neodymium-doped yttrium aluminum garnet (Nd-YAG) laser results in emission of photocoagulating 532 nm light compared with photolytic 1064 nm emission. The ergonomic benefits of solid-state lasers led to replacement of older coagulating lasers in ophthalmic centres by frequency-doubled Nd-YAG laser. Our study aims to evaluate safety and efficacy of frequency-doubled Nd-YAG laser for photocoagulation of corneal neovascularisation (NLPC).Methods 30 quiet eyes of 28 patients with superficial, mid-stromal and deep stromal inactive corneal neovascularisation were subjected to laser photocoagulation. Resolution of vessels, procedural complications and survival of subsequent corneal grafts were monitored for 3 months. Anterior segment fluorescein angiography (AS-FA) was performed in six eyes to confirm the cessation of blood flow.Results 20 eyes (66.66%) had complete resolution of neovascularisation. 13 cases of superficial (92.86%) and 6 cases of mid-stromal neovascularisation (75%) showed significant resolution, compared with 1 case of deep neovascularisation (12.5%). Minimal corneal burn (n=4, 13.33%), iris holes (n=3, 10%), anterior chamber bubbles (n=5, 16.67%), self-resolving intrastromal bleed (n=2, 6.67%) and graft-host junctional wound leak (n=1 of 12 keratoplasty cases, 8.33%) were noted.Conclusion NLPC may especially be useful in the eyes with a large vessel arborising within stroma. Lack of comparison with other treatment options leading to inflated safety and efficacy profile of NLPC is the major limitation of this study.